How shareholder activism influences company non-financial performance. - Cundill, Gary (Cranfield University, 2018)
Shareholders have become increasingly active in endeavouring to influence companies’ non-financial performance, but enquiries into this form of shareholder activism are limited and fragmented. It is as yet unclear what aspects of company non-financial performance are of most interest to shareholders. Researchers have yet to uncover the conditions under which shareholder interventions succeed, or how boards respond beyond simple increases in disclosure. Furthermore, research in emerging markets is almost non-existent. This thesis addresses these gaps in two main ways. First, a systematic literature review provides a synthesis of the state of academic knowledge about shareholder activism that aims to influence corporate environmental and social performance. Theoretical perspectives appropriate to this phenomenon are critically appraised, and data from the literature are organised into a new process model of shareholder influence. An agenda to direct future research in this burgeoning field is articulated. Second, an empirical study investigates non-financial shareholder activism in the context of companies listed on the Johannesburg Stock Exchange, drawing on interviews with a range of participants, as well as media reports and company documentation. An enhanced process model of the phenomenon is proposed that details a broad range of shareholder interventions, and shows how their impact is moderated by several variables. A typology of directors’ actions and concomitant outcomes is detailed, showing the presence of a feedback loop to the factors moderating the process. A set of environmental, social and governance (ESG) issues of interest to contemporary shareholders is presented, showing what shareholders believe constitute company non-financial performance. Insight is provided into contradictions in the concept of ESG, particularly in the conflation of company environmental and social performance and company governance processes. A concluding discussion then explains how this two-pronged approach has enriched the existing knowledge base, implications for practitioners are provided and an enhanced research agenda is offered.
Keywords: Non-financial shareholder activism; corporate environmental performance; corporate social performance; corporate governance; corporate social responsibility; ESG